1995
DOI: 10.1063/1.358696
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of electron transport in gallium nitride

Abstract: Articles you may be interested inA detailed characterization of the transient electron transport within zinc oxide, gallium nitride, and gallium arsenide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…4 is in a range of 10 4 -10 6 cm −2 , which is the lowest ever reported. simulations [19][20][21]23,27 and actual measurement. 33,34 The curves show two distinct regions across a peak drift velocity signifying the migration of electron into the higher M-L valleys for high electric fields.…”
Section: A Forward Conductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 is in a range of 10 4 -10 6 cm −2 , which is the lowest ever reported. simulations [19][20][21]23,27 and actual measurement. 33,34 The curves show two distinct regions across a peak drift velocity signifying the migration of electron into the higher M-L valleys for high electric fields.…”
Section: A Forward Conductionmentioning
confidence: 99%
“…Different Monte Carlo calculation methods like the full potential linearized augmented plane wave (FLAPW), 12 orthogonalized linear combination of atomic orbitals (OLCAO) 13 or the empirical pseudo potential method (EPM) 14 are used to determine the band structure and hole and electron effective masses. 12,[14][15][16][17] Similar Monte Carlo calculations are performed to determine the bulk electron [18][19][20][21][22][23][24][25][26][27] and hole [28][29][30][31] mobility employing different band structure and scattering mechanisms. Although experimentally determined values of electron mobility [32][33][34][35] are reported there are few available experimental data for hole mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Gelmont et al (1993) reported on ensemble two-valley Monte Carlo simulations of the electron transport within bulk wurtzite GaN. Mansour et al (1995) reported the use of such an approach in order to determine how the crystal temperature influences the velocity-field characteristic associated with bulk wurtzite GaN. Kolník et al (1995) reported on employing full-band Monte Carlo simulations of the electron transport within bulk wurtzite GaN and bulk zincblende GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]). Meanwhile, such basic properties of the nitrides such as relatively low effective masses, high optical phonon energies, strong electron-optical phonon interaction and large energy separations of the upper valleys bring about a number of new hot electron effects in moderate electric fields.…”
mentioning
confidence: 99%